Investigation and Survey on the Standardization of China's carbon emission trading market Based on the Government Demand Analysis. Issue 5 (August 2019) - Guo, Huiting; Liu, Mei; Yang, Ming; Zhang, Sinan; Zhao, Xuezhi
Abstract: In 2017, China's carbon emission trading market was officially launched. This paper summarizes the work of the seven carbon emission trading pilots and the implementation progresses of the key industries that participated in the program. This work serves as an important basis to support the establishment of the standard system of China's carbon emission trading market.